Initial data release and announcement of the 10, 000 Fish Genomes Project (Fish10K). Issue 8 (18th August 2020) - Fan, Guangyi; Song, Yue; Yang, Liandong; Huang, Xiaoyun; Zhang, Suyu; Zhang, Mengqi; Yang, Xianwei; Chang, Yue; Zhang, He; Li, Yongxin; Liu, Shanshan; Yu, Lili; et al.
Abstract: Background: With more than 30, 000 species, fish—including bony, jawless, and cartilaginous fish—are the largest vertebrate group, and include some of the earliest vertebrates. Despite their critical roles in many ecosystems and human society, fish genomics lags behind work on birds and mammals. This severely limits our understanding of evolution and hinders progress on the conservation and sustainable utilization of fish. Results: Here, we announce the Fish10K project, a portion of the Earth BioGenome Project aiming to sequence 10, 000 representative fish genomes in a systematic fashion within 10 years, and we officially welcome collaborators to join this effort. As a step towards this goal, we herein describe a feasible workflow for the procurement and storage of biospecimens, as well as sequencing and assembly strategies. Conclusions: To illustrate, we present the genomes of 10 fish species from a cohort of 93 species chosen for technology development.